Awareness of dementia and coping to preserve quality of life: a five-year longitudinal narrative study. Issue 1 (1st January 2020) - Thorsen, Kirsten; Dourado, Marcia C. N.; Johannessen, Aud
ABSTRACT: Purpose: To examine how people (<65 years) with young-onset dementia (YOD) express awareness of dementia and how they seem to handle awareness as a strategy to preserve quality of life over time. Method: A longitudinal qualitative study with individuals with YOD was performed with interviews every 6 months over 5 years for a maximum of 10 interviews. The interviews were analysed by modified grounded theory adapted to narrative inquiry. Results: Awareness is a complex, multidimensional concept. Awareness of dementia is predisposed by personality, life history and established coping styles. The main coping styles during dementia—live in the moment, ignore the dementia, and make the best of it—seem to be rather consistent throughout disease progression. Transitions in the life situation may change the individual's awareness of dementia. Conclusion: Unawareness of dementia may have an important adaptive function for preserving quality of life. Increasing awareness of dementia must be approached with reflexivity and great sensitivity.